Method for preparing boron-based composite particles containing high-energy compound
By mixing boron powder with high-energy compounds in nitrocellulose solution to form closely constrained composite particles, the problems of weak interface binding capacity and low combustion efficiency in the prior art are solved, and the combustion efficiency and heat value are significantly improved effect.
Patent Information
- Application Number
- CN202411576685.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, boron-rich fuels have problems with weak interface binding capacity and low combustion efficiency.
By using a method of preparing boron-based composite particles containing high energy compounds, boron powder is combined with 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine or cyclotetradene The base tetranitinamine is mixed in a nitrocellulose solution and treated in a surfactant solution to form closely bound composite particles.
The combustion efficiency and combustion calorific value of boron powder are significantly improved, the heat transfer effect of composite particles is enhanced, the oxidation temperature of boron powder is reduced, and the interface bonding ability during combustion is improved.
Smart Images

Figure CN119391465A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energetic materials, and in particular relates to a method for preparing boron-based composite particles containing high-energy compounds. Background Art
[0002] Boron powder has broad application prospects in the fuel field due to its high mass calorific value and volume calorific value. It is used as a combustion agent, or boron-rich fuel is used as a power source for ramjet engines. Its combustion effect and energy release efficiency seriously affect the load and maneuverability of ramjet engines.
[0003] The surface of boron powder has an oxide layer with low melting temperature and high volatilization temperature, and absorbs moisture in the air to produce a small amount of boric acid crystals. The presence of these impurities seriously hinders the combustion process of boron powder and significantly reduces its combustion efficiency. How to effectively solve these obstacles in the combustion process of boron powder has become the focus of current research. At present, various functional components such as energetic materials, fluorine-containing compounds, and metal oxides are used for interface modification. Under the action of functional components, boron oxide is converted into solid / gas phase products or accelerates the departure process of boron oxide, which enhances the combustion effect of boron powder to a certain extent. However, the methods currently reported have defects such as weak interface bonding ability and complex preparation methods, and cannot be used for large-scale production. Summary of the invention
[0004] In order to overcome the problems of weak interface bonding ability and low combustion efficiency of boron-rich fuel in the prior art, the purpose of the present invention is to provide a method for preparing boron-based composite particles containing high-energy compounds, effectively introducing high-nitrogen energetic materials and high-energy explosives. The method is simple to operate and has a stable preparation process. The units in the prepared composite particles are tightly fitted, the interface bonding ability is enhanced, the combustion efficiency is significantly improved, and the composite particles have good dispersibility and are easier to further process and apply.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing boron-based composite particles containing high-energy compounds comprises the following steps:
[0007] Adding boron powder and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine to a nitrocellulose solution, or adding boron powder and cyclotetramethylene tetranitramine to a nitrocellulose solution to obtain a mixed solution;
[0008] The mixed solution is added into a surfactant solution at 60-65° C. to obtain boron-based composite particles containing high-energy compounds.
[0009] Furthermore, the particle size of the metal boron powder is 0.5-2 μm, the nitrogen content of nitrocellulose is 12.4%, the nitrogen content of 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine is 79.1%, and the nitrogen content of cyclotetramethylene tetranitramine is 37.8%.
[0010] Furthermore, the solvent in the nitrocellulose solution is ethyl acetate.
[0011] Furthermore, the amount of boron powder used is 70wt% to 90wt% of the total mass of nitrocellulose, boron powder and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine; the amount of boron powder used is 70wt% to 90wt% of the total mass of nitrocellulose, boron powder and cyclotetramethylene tetranitramine.
[0012] Furthermore, the amount of 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine used is 10wt% to 20wt% of the mass of nitrocellulose, boron powder and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine.
[0013] Furthermore, the amount of cyclotetramethylene tetranitramine used is 10wt% to 20wt% of the mass of nitrocellulose, boron powder and cyclotetramethylene tetranitramine.
[0014] Furthermore, the surfactant is sodium dodecylbenzene sulfonate.
[0015] Furthermore, the mass concentration of the surfactant solution is 0.2 wt %.
[0016] Furthermore, the mixed solution is added into a surfactant solution at 60-65° C. by a dropwise addition method.
[0017] A boron-based composite particle containing a high-energy compound.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The boron-based composite particles prepared by the present invention can significantly improve the combustion efficiency and combustion heat value of boron powder. The method forms a network structure by the precipitation of nitrocellulose in an anti-solvent, and the boron powder and 4,4,-6,6-tetra (azido) hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) are adhered and tightly constrained to form uniform composite particles. The auxiliary agent and the boron powder are evenly distributed and tightly constrained in the nitrocellulose network, and the contact between the interfaces is greatly improved. At the same time, the configuration enhances the heat transfer effect of the composite particles and reduces the oxidation temperature of the boron powder. In addition, the compatibility of nitrocellulose and 4,4,-6,6-tetra (azido) hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) is improved, and can synergistically act to accelerate the departure of boron oxide. The synthesis method of the present invention is safe, simple, efficient, and easy to industrialize.
[0020] Furthermore, the irregular morphology of boron powder will affect the particle forming process, so micron-sized particles with a particle size range of 0.5-2 μm are selected.
[0021] Furthermore, nitrocellulose, as an energetic and adhesive polymer material, is very suitable for use as an auxiliary agent for modified boron powder. In addition, nitrocellulose has a rigid six-membered ring in its molecular structure, which has a strong auxiliary effect on the forming ability of composite particles. Therefore, nitrocellulose is selected as the binder, and the concentration of the nitrocellulose solution is 0.016-0.025g / ml.
[0022] Furthermore, 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) as an energetic compound can generate a large amount of gas and carbon source during the combustion process, stripping boron oxide from the active boron surface and reacting with the carbon source to form solid phase particles. Therefore, 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) is selected as another modification auxiliary agent, and its content accounts for 0wt%-20wt% of the total amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 These are morphology pictures of the boron-based composite particles in Example 2, Example 4, and Comparative Example 2 of the present invention; wherein (a) is the surface morphology of BN in Comparative Example 2; (b) is the surface morphology of BNT-2 in Example 2; (c) is the surface morphology of BNH-2 in Example 4; and (d) is the morphology and thickness of the shell.
[0024] Figure 2 It is an X-ray diffraction curve diagram of the boron powder in the present invention and the boron-based composite particles in Example 2, Example 4 and Comparative Example 2;
[0025] Figure 3It is the Fourier infrared change graph of the boron powder in the present invention and the boron-based composite particles in Example 2, Example 4 and Comparative Example 2;
[0026] Figure 4 It is a low temperature DSC curve diagram of the boron powder in the present invention and the boron-based composite particles in Examples 1-4 and Comparative Example 2;
[0027] Figure 5 The high temperature DSC graphs of the boron powder in the present invention and the boron-based composite particles in Example 2, Example 4 and Comparative Example 2;
[0028] Figure 6 The ignition temperature curves of the boron powder in the present invention and the boron-based composite particles in Example 2, Example 4 and Comparative Example 2;
[0029] Figure 7 The figure is a bar graph showing the combustion heat and combustion efficiency of the boron powder of the present invention and the boron-based composite particles of Examples 1-4 and Comparative Example 2.
[0030] Figure 8 This is a snapshot of the combustion flame of the boron powder in the present invention.
[0031] Fig. 9 This is a snapshot of the combustion flame of the boron-based composite particles in Comparative Example 2 of the present invention.
[0032] Fig.10 This is a snapshot of the combustion flame of the boron-based composite particles in Example 1 of the present invention.
[0033] Fig.11 This is a snapshot of the combustion flame of the boron-based composite particles in Example 2 of the present invention.
[0034] Fig.12 This is a snapshot of the combustion flame of the boron-based composite particles in Example 3 of the present invention.
[0035] Fig.13 This is a snapshot of the combustion flame of the boron-based composite particles in Example 4 of the present invention.
[0036] Fig.14 B1s fine spectrum of the boron powder residue in the present invention.
[0037] Fig.15 This is the B1s fine spectrum of the BN residue of Comparative Example 2 of the present invention.
[0038] Fig.16 The B1s fine spectrum of the BNT-2 residue of Example 2 of the present invention
[0039] Fig.17 This is the B1s fine spectrum of the BNH-2 residue of Example 4 of the present invention. DETAILED DESCRIPTION
[0040] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0041] In order to solve the problem of low efficiency and incomplete combustion of boron powder, the present invention prepares a boron-based composite particle containing a high-energy compound.
[0042] A method for preparing boron-based composite particles containing high-energy compounds of the present invention is: adding nitrocellulose to solvent ethyl acetate and stirring for 1 hour to prepare solution A. The concentration of solution A is 0.016-0.025 g / ml.
[0043] Add boron powder and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) into solution A successively and stir for 8-12 hours to obtain a mixed solution C.
[0044] Aspirate solution C with a syringe and connect it to a peristaltic pump. The pump speed is 10 mL / h. -1 , the water phase temperature is set to 60-65° C. Solution C is dripped into the water phase solution (the surfactant added to the deionized water is sodium dodecylbenzene sulfonate (SDBS), and the amount of the surfactant is 0.2wt% of the mass of the deionized water) through a stainless steel needle, during which the water phase temperature is maintained at 60-65° C. After solidification, oil-in-water micelle particles are obtained, the oil-in-water micelle particles are collected and washed with water for multiple times, and finally dried to obtain boron-based composite particles containing high-energy compounds.
[0045] The particle size of the metal boron powder in the present invention is 0.5-2 μm, the nitrogen content (atomic mass content) of nitrocellulose is 12.4%, the nitrogen content (atomic mass content) of 4,4,-6,6-tetrakis (azido) hydrazine-1,3,5-triazine is 79.1%, and the nitrogen content (atomic mass content) of cyclotetramethylene tetranitramine is 37.8%.
[0046] In the present invention, the amount of boron powder used is 70wt% to 90wt% of the total amount (nitrocellulose, boron powder and 4,4,-6,6-tetrakis (azido) hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine), and the amount of 4,4,-6,6-tetrakis (azido) hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) used is 10wt% to 20wt% of the total amount (the mass of nitrocellulose, boron powder and 4,4,-6,6-tetrakis (azido) hydrazine-1,3,5-triazine).
[0047] The boron-based composite particles containing high-energy compounds prepared by the present invention can greatly improve the combustion efficiency and combustion heat of boron powder.
[0048] Example 1
[0049] (1) Dissolve 0.1 g of nitrocellulose in 4 mL of ethyl acetate solution and stir for 1 h to obtain nitrocellulose solution A; weigh 0.8 g of boron powder and 0.1 g of 4,4-tetrakis(azido)hydrazine-1,3,5-triazine and add them to solution A successively and stir for 8 h to obtain a mixed solution C;
[0050] (2) The stirred solution was sucked into a syringe and the bubbles were expelled by oscillation; the precursor solution C was squeezed into an aqueous solution at 60° C. (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt %) through a stainless steel needle at a rate of 10 ml / h, and the solidified particles were collected and washed with deionized water, and dried in an oven at 50° C. to obtain boron-based composite particles containing high-energy compounds, named BNT-1;
[0051] At an extrusion rate of 10 ml / h, the droplets can be quickly filled and formed, the droplets condense at the needle tip and detach during droplet formation. In the 60°C aqueous phase, the nitrocellulose precipitates from the solution and binds the loose boron powder particles and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine particles into large particles. The large particles rotate in the aqueous solution to continuously evaporate the ethyl acetate solvent.
[0052] from Figure 1 From the morphologies of (a), (b), (c) and (d), it can be observed that the surfaces of the three composite particles prepared are porous, which are the holes left by the ethyl acetate during the rotary evaporation process. The porous structure is more conducive to mass transfer and heat transfer. The structure of the shell layer shows that the boron powder and 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) are tightly bound to form a uniform three-dimensional structure.
[0053] from Figure 2 , Figure 3 It can be seen from the functional group results and crystal structure results that the composite particles prepared by this method contain 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine (cyclotetramethylenetetranitramine) components and nitrocellulose components.
[0054] from Figure 4 It can be observed that nitrocellulose and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) components have good compatibility, and the decomposition peaks of the two substances are close to the middle. Therefore, the synergistic effect of the two can better enhance the combustion performance of boron powder.
[0055] Figure 5 It can be seen that the thermal oxidation temperatures of the composite particles of the two components BNT-1 and BNH-1 are similar, which is ~15°C lower than that of the B powder and ~3°C lower than that of the BN component. This shows that the addition of 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) further reduces the thermal oxidation temperature of the boron powder.
[0056] Figure 6 It can be seen that the ignition temperature of BNT-1 is 726℃, which is 46.7℃ lower than that of B powder and 2.2℃ lower than that of BNH-1 (728.2℃). The ignition temperatures of the two composite particles are 8.2℃ and 6℃ lower than those of BN particles, respectively. The effect of adding 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine is stronger than that of cyclotetramethylene tetranitramine, but the ignition temperature is greatly reduced overall.
[0057] from Figure 7 It can be seen that the combustion heat of the BNT composite particles prepared by this method is higher than that of the original B powder, and the combustion efficiency is increased to 78.06% and 88.66% respectively. This is because the carbon content in cyclotetramethylene tetranitramine is higher than that in 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine, and the carbon source produced during the decomposition process is richer. Therefore, the oxidation of boron is more complete.
[0058] The above results can be obtained from Fig.14 , Fig.15 , Fig.16 and Fig.17 As confirmed by the results, the peak intensity of B in the residue of BNT-2 is lower than that in the residue of BNH-2, while BN, BNT-2 and BNH-2 all significantly increased the oxidation degree of B.
[0059] Figure 8 , Fig. 9 , Fig.10 , Fig.11 , Fig.12 and Fig.13 In order to conduct ignition experiments on the four composite particles, as the content of 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine increases, the deflagration phenomenon generated at the moment of ignition intensifies, and the burning particles splash, which is a great advantage for boron powder to contact oxygen. The deflagration phenomenon generated by the addition of cyclotetramethylene tetranitramine is significantly weaker, and it is the oxidizing atmosphere provided by cyclotetramethylene tetranitramine that promotes the expansion of the flame. Therefore, the BNH-1 and BNH-2 components produce obvious green flames. The addition of 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine promotes the splashing of burning particles, thereby making the combustion complete, which is consistent with the conclusion of high combustion calorific value.
[0060] Example 2
[0061] (1) Dissolve 0.1 g of nitrocellulose in 4 mL of ethyl acetate solution and stir for 1 h to obtain nitrocellulose solution A; weigh 0.7 g of boron powder and 0.2 g of 4,4-tetrakis(azido)hydrazine-1,3,5-triazine, add them to solution A and stir for 8 h to obtain a mixed solution C;
[0062] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by shaking; the precursor solution C is squeezed into an aqueous solution at 60° C. (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt %) through a stainless steel needle at a rate of 10 ml / h, and the obtained solidified particles are collected and washed with deionized water, and dried in an oven at 50° C. to obtain boron-based composite particles containing high-energy compounds, named BNT-2;
[0063] At an extrusion rate of 10 ml / h, the droplets can be quickly filled and formed, the droplets condense at the needle tip and detach during droplet formation. In the 60°C aqueous phase, the nitrocellulose precipitates from the solution and binds the loose boron powder particles and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine particles into large particles. The large particles rotate in the aqueous solution to continuously evaporate the ethyl acetate solvent.
[0064] Example 3
[0065] (1) Dissolve 0.1 g of nitrocellulose in 4 mL of ethyl acetate solution and stir for 1 h to obtain nitrocellulose solution A; weigh 0.8 g of boron powder and 0.1 g of cyclotetramethylene tetranitramine, add them to solution A and stir for 8 h to obtain a mixed solution C;
[0066] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by oscillation; the precursor solution C is squeezed into an aqueous solution at 60° C. (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt %) through a stainless steel needle at a rate of 10 ml / h, the solidified particles are collected and washed with deionized water, and dried in an oven at 50° C. to obtain boron-based composite particles containing high-energy compounds, named BNH-1;
[0067] At an extrusion rate of 10 ml / h, the droplets can be quickly filled and formed, the droplets condense at the needle tip and detach during droplet formation. In the 60°C aqueous phase, the nitrocellulose precipitates from the solution and binds the loose boron powder particles and cyclotetramethylene tetranitramine particles into large particles. The large particles rotate in the aqueous solution to continuously evaporate the ethyl acetate solvent.
[0068] from Figure 2 , Figure 3It can be seen from the functional group results and the crystal structure results that the composite particles prepared by this method contain cyclotetramethylene tetranitramine components and nitrocellulose components.
[0069] Example 4
[0070] (1) Dissolve 0.1 g of nitrocellulose in 4 mL of ethyl acetate solution and stir for 1 h to obtain nitrocellulose solution A; weigh 0.7 g of boron powder and 0.2 g of cyclotetramethylene tetranitramine, add them to solution A and stir for 8 h to obtain a mixed solution C;
[0071] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by shaking; the precursor solution C is squeezed into an aqueous solution at 60° C. (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt %) through a stainless steel needle at a rate of 10 ml / h, the solidified particles are collected and washed with deionized water, and dried in an oven at 50° C. to obtain boron-based composite particles containing high-energy compounds, named BNH-2;
[0072] At an extrusion rate of 10 ml / h, the droplets can be quickly filled and formed, the droplets condense at the needle tip and detach during droplet formation. In the 60°C aqueous phase, the nitrocellulose precipitates from the solution and binds the loose boron powder particles and cyclotetramethylene tetranitramine particles into large particles. The large particles rotate in the aqueous solution to continuously evaporate the ethyl acetate solvent.
[0073] Example 5
[0074] (1) 0.1 g of nitrocellulose was dissolved in ethyl acetate solution and stirred for 1 h to obtain a 0.016 g / ml nitrocellulose solution A; 0.75 g of boron powder and 0.15 g of cyclotetramethylene tetranitramine were weighed and added to solution A successively and stirred for 8 h to obtain a mixed solution C;
[0075] (2) The uniformly stirred solution is sucked into a syringe and the bubbles are expelled by oscillation. The precursor solution C is squeezed into an aqueous solution at 62°C (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt%) through a stainless steel needle at a rate of 10 ml / h. The solidified particles are collected and washed with deionized water, and dried in an oven at 50°C to obtain boron-based composite particles containing high-energy compounds.
[0076] Example 6
[0077] (1) 0.1 g of nitrocellulose was dissolved in ethyl acetate solution and stirred for 1 h to obtain a solution A of 0.020 g / ml nitrocellulose; 0.73 g of boron powder and 0.17 g of cyclotetramethylene tetranitramine were weighed and added to solution A successively and stirred for 8 h to obtain a mixed solution C;
[0078] (2) The uniformly stirred solution is sucked into a syringe and shaken to expel bubbles; the precursor solution C is squeezed into an aqueous solution at 65°C (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt%) through a stainless steel needle at a rate of 10 ml / h, the resulting solidified particles are collected and washed with deionized water, and dried in an oven at 50°C to obtain boron-based composite particles containing high-energy compounds.
[0079] Comparative Example 1
[0080] (1) Dissolve 0.1 g of nitrocellulose in 6 mL of ethyl acetate solution and stir for 1 h to obtain nitrocellulose solution A; weigh 0.9 g of boron powder and add it to solution A and stir for 8 h to obtain a mixed solution B;
[0081] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by oscillation; the precursor solution C is squeezed into an aqueous solution at 60° C. (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt %) through a stainless steel needle at a rate of 12 ml / h, and the obtained solidified particles are collected and washed with deionized water, and dried in an oven at 50° C.;
[0082] At an extrusion rate of 12 ml / h, the droplets can be quickly filled and formed, and the droplets condense at the needle tip. However, due to the low solid content of the droplets, the droplets are dispersed into multiple small droplets. In the 60°C aqueous phase, the nitrocellulose precipitates from the solution and binds the loose boron powder particles into large particles. The large particles rotate in the aqueous solution and continue to evaporate the ethyl acetate solvent. In the preparation process of this method, the small droplets at the needle tip can easily float to the water surface, thereby spreading on the water surface, which will continuously affect the formation of droplets under the liquid surface. Therefore, the extrusion rate selected in the present invention is 10 mL·h -1 .
[0083] Comparative Example 2
[0084] (1) Dissolve 0.1 g of nitrocellulose in 4 mL of ethyl acetate solution and stir for 1 h to obtain nitrocellulose solution A; weigh 0.9 g of boron powder and add it to solution A and stir for 8 h to obtain a mixed solution B;
[0085] (2) The stirred solution was sucked into a syringe and the bubbles were expelled by oscillation; the precursor solution C was squeezed into an aqueous solution at 60° C. (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt %) through a stainless steel needle at a rate of 10 ml / h, and the obtained solidified particles were collected and washed with deionized water, and dried in an oven at 50° C. to obtain particles, which were named BN;
[0086] At an extrusion rate of 10 ml / h, the droplets can be quickly filled and formed, the droplets condense at the needle tip and detach during droplet formation. In the 60°C aqueous phase, the nitrocellulose precipitates from the solution and binds the loose boron powder particles into large particles. The large particles rotate in the aqueous solution to continuously evaporate the ethyl acetate solvent.
[0087] Figure 5 It can be seen that the thermal oxidation temperature of the BN component is 12°C earlier than that of the B powder.
[0088] from Figure 6 It can be seen that the ignition temperature of the BN component is 38°C lower than that of the B powder.
[0089] from Figure 7 It can be seen that the combustion heat of the composite particles prepared by this method is 39.12 KJ / g, and the combustion efficiency is increased to 73.8%. However, the reduction in ignition temperature is too small, and the combustion effect on boron powder is not significant.
[0090] from Figure 8-Figure 13 It can be seen that the flame of the BN component is weak and the combustion effect is not significantly improved. Therefore, adding only nitrocellulose has no obvious effect on the combustion of boron powder. Therefore, it is necessary to add 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine or cyclotetramethylene tetranitramine in the present invention.
[0091] Comparative Example 3
[0092] (1) Dissolve 0.1 g of nitrocellulose in 4 mL of ethyl acetate solution and stir for 1 h to obtain nitrocellulose solution A; weigh 0.8 g of boron powder and 0.1 g of 4,4-tetrakis(azido)hydrazine-1,3,5-triazine and add them to solution A successively and stir for 8 h to obtain a mixed solution C;
[0093] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by oscillation; the precursor solution C is squeezed into an aqueous solution (aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt%) at 70° C. through a stainless steel needle at a rate of 10 ml / h, and the obtained solidified particles are collected and washed with deionized water, and dried in an oven at 50° C.;
[0094] At an extrusion rate of 10 ml / h, the droplets can be quickly filled and formed, and the droplets are condensed at the needle tip and separated during droplet formation. In the 70°C aqueous phase, nitrocellulose precipitates from the solution and binds the loose boron powder particles and 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine particles into large particles. The large particles rotate in the aqueous phase solution to continuously volatilize the ethyl acetate solvent. However, due to the high temperature of the aqueous phase, the particles are softened by heat and collided and loosened in the aqueous phase solution during the solution extrusion process, and the forming degree is too low, so it is not suitable at this temperature, so the temperature selected in the present invention is 60-65°C.
[0095] Comparative Example 4
[0096] (1) Dissolve 0.1 g of nitrocellulose in 6 mL of ethyl acetate solution and stir for 1 h to obtain nitrocellulose solution A; weigh 0.9 g of boron powder and add it to solution A and stir for 8 h to obtain a mixed solution C;
[0097] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by shaking; the precursor solution C is squeezed into an aqueous solution at 50° C. (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt %) through a stainless steel needle at a rate of 8 ml / h, and the obtained solidified particles are collected and washed with deionized water, and dried in an oven at 50° C.;
[0098] At an extrusion rate of 8 ml / h, the droplet formation speed is slow, the droplet breaks at the needle tip, and no suitable particles can be obtained. Therefore, this parameter (extrusion rate) is not appropriate.
[0099] Comparative Example 5
[0100] (1) Dissolve 0.1 g of nitrocellulose in 6 mL of ethyl acetate solution and stir for 1 h to obtain nitrocellulose solution A; weigh 0.9 g of boron powder and add it to solution A and stir for 8 h to obtain a mixed solution C;
[0101] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by shaking; the precursor solution C is squeezed into an aqueous solution at 50° C. (an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt %) through a stainless steel needle at a rate of 10 ml / h, and the obtained solidified particles are collected and washed with deionized water, and dried in an oven at 50° C.;
[0102] At an extrusion rate of 10 ml / h, droplets can be formed quickly, condensed at the needle tip and separated during droplet formation. However, due to the low temperature of the water phase, the particles cannot be solidified quickly, and the droplets adhere and no suitable particles can be obtained. Therefore, this parameter (water phase temperature) is not appropriate.
[0103] Comparative Example 6
[0104] (1) Dissolve 0.1 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) in 4 mL of ethyl acetate solution and stir for 1 h to obtain PVDF-HFP solution A; weigh 0.8 g of boron powder and 0.1 g of TAHT, add them to solution A and stir for 8 h to obtain a mixed solution C;
[0105] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by shaking; the precursor solution C is squeezed into an aqueous solution (aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt%) at 60° C. through a stainless steel needle at a rate of 10 ml / h, and the obtained solidified particles are collected and washed with deionized water, and dried in an oven at 50° C.;
[0106] PVDF-HFP as a binder cannot provide sufficient support, the sphericity of the particles is reduced, and the surface is bumpy, so nitrocellulose needs to be selected as a binder in the present invention.
[0107] Comparative Example 7
[0108] (1) Dissolve 0.1 g of polyvinyl chloride (PVVA) in 4 mL of acetone solution and stir for 1 h to obtain PVVA solution A; weigh 0.8 g of boron powder and 0.1 g of TAHT, add them to solution A and stir for 8 h to obtain a mixed solution C;
[0109] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by shaking; the precursor solution C is squeezed into an aqueous solution (aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt%) at 60° C. through a stainless steel needle at a rate of 10 ml / h, and the obtained solidified particles are collected and washed with deionized water, and dried in an oven at 50° C.;
[0110] PVVA as a binder cannot provide sufficient support, and the particles cannot be formed. In addition, acetone and water are miscible, and PVVA precipitates quickly when it meets water and spreads on the water phase interface. No regular spherical particles appear in the water phase, and all that is collected are broken particles. Therefore, nitrocellulose needs to be selected as a binder in the present invention.
[0111] Comparative Example 8
[0112] (1) 0.1 g of polyvinyl pyrrolidone (PVP) was dissolved in 4 mL of acetone solution and stirred for 1 h to obtain PVP solution A; 0.8 g of boron powder and 0.1 g of TAHT were weighed and added to solution A successively and stirred for 8 h to obtain a mixed solution C;
[0113] (2) The stirred solution is sucked into a syringe and the bubbles are expelled by shaking; the precursor solution C is squeezed into an aqueous solution (aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 0.2 wt%) at 60° C. through a stainless steel needle at a rate of 10 ml / h, and the obtained solidified particles are collected and washed with deionized water, and dried in an oven at 50° C.;
[0114] The structure of PVP can be used as a rigid binder, but its water-soluble properties prevent it from becoming micellar particles and solidifying in the aqueous phase. Instead, PVP is precipitated by the solvent-antisolvent method, and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine is adhered and fixed by PVP along with boron powder. Therefore, nitrocellulose needs to be selected as the binder in the present invention.
[0115] In Examples 1-6 and Comparative Examples 5-8, four system binders, namely nitrocellulose, PVDF-HFP, PVVA, and PVP, were used for trial. Since some of the selected polymers are insoluble in ethyl acetate and can only be dissolved in acetone, and acetone and water are mutually soluble, spherical particles cannot be obtained. In addition, PVVA and PVDF-HFP are linear structure polymers, and as a network structure, their chains are not rigid enough to support particle formation. Among the four selected polymers, only the nitrocellulose long chain itself has a rigid six-membered ring, which can be used as a supporting structure and can be dissolved in ethyl acetate to adapt to this method. In addition, it contains energy itself, produces gas and releases carbon source during the decomposition process, so nitrocellulose is more suitable for this system.
[0116] The method for preparing boron-based composite microparticles containing high-energy compounds can enhance the combustion efficiency of boron powder to a certain extent, and provide a basis for subsequent applications.
[0117] Most of the modification methods reported so far are based on surface loading, and functional additives are adsorbed onto the surface of boron powder through electrostatic interaction. In this way, the binding ability between interfaces is weak, and the additives only act on the surface of boron powder. During the combustion process, the additives will be separated from the boron powder, so the auxiliary effect is limited. In this method, the boron powder and 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine (or cyclotetramethylene tetranitramine) are adhered and tightly constrained into uniform composite particles through the network structure formed by the precipitation of nitrocellulose in the anti-solvent. The additives and boron powder are evenly distributed and tightly constrained in the nitrocellulose network. This configuration enhances the heat transfer effect of the composite particles and reduces the oxidation temperature of the boron powder. In addition, the compatibility of nitrocellulose and 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine (cyclotetramethylene tetranitramine) is improved, which can synergistically accelerate the departure of boron oxide. The synthesis method of the present invention is safe, simple, efficient, and easy to industrialize.
[0118] The present invention uses energetic binder nitrocellulose as a support system, and adds 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine or cyclotetramethylene tetranitramine as a combustion aid to further enhance the combustion of boron powder. Nitrocellulose itself has a six-membered rigid carbon ring, which can provide support when used as a binder, which is conducive to the molding of spherical particles. In addition, the decomposition of nitrocellulose releases heat flow and carbon source. Heat flow can accelerate the phase change process of the oxide layer of boron powder and further enhance oxidation. The carbon source can weaken the adhesion state of the oxide layer and further promote combustion. 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine or cyclotetramethylene tetranitramine itself decomposes to release energy and release a large amount of gas. The impact of the heat flow weakens the adhesion state of the oxide layer, exposes the active boron to oxygen, and provides a good environmental atmosphere for the combustion of boron powder. In addition, nitrocellulose has good compatibility with 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine or cyclotetramethylene tetranitramine, and the synergistic effect of the two further promotes the combustion of boron powder.
[0119] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0120] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a boron-based composite microstructure containing a high-energy compound, characterized in that: The following steps are involved: Adding boron powder and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine to a nitrocellulose solution, or adding boron powder and cyclotetramethylene tetranitramine to a nitrocellulose solution to obtain a mixed solution; The mixed solution is added into a surfactant solution at 60-65° C. to obtain boron-based composite particles containing high-energy compounds.
2. The method for preparing boron-based composite particles containing high-energy compounds according to claim 1, characterized in that: The particle size of the metal boron powder is 0.5-2 μm, the nitrogen content of the nitrocellulose is 12.4%, the nitrogen content of the 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine is 79.1%, and the nitrogen content of the cyclotetramethylene tetranitramine is 37.8%.
3. The method for preparing boron-based composite particles containing high-energy compounds according to claim 1, characterized in that: The solvent in the nitrocellulose solution is ethyl acetate.
4. The method for preparing boron-based composite particles containing high-energy compounds according to claim 1, characterized in that: The amount of boron powder used is 70wt% to 90wt% of the total mass of nitrocellulose, boron powder and 4,4,-6,6-tetra(azido)hydrazine-1,3,5-triazine; the amount of boron powder used is 70wt% to 90wt% of the total mass of nitrocellulose, boron powder and cyclotetramethylene tetranitramine.
5. The method for preparing boron-based composite particles containing high-energy compounds according to claim 1, characterized in that: The amount of 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine used is 10wt% to 20wt% of the mass of nitrocellulose, boron powder and 4,4,-6,6-tetrakis(azido)hydrazine-1,3,5-triazine.
6. The method for preparing boron-based composite particles containing high-energy compounds according to claim 1, characterized in that: The dosage of cyclotetramethylene tetranitramine is 10wt% to 20wt% of the mass of nitrocellulose, boron powder and cyclotetramethylene tetranitramine.
7. The method for preparing boron-based composite particles containing high-energy compounds according to claim 1, characterized in that: The surfactant is sodium dodecylbenzene sulfonate.
8. The method for preparing boron-based composite particles containing high-energy compounds according to claim 1, characterized in that: The mass concentration of the surfactant solution is 0.2 wt %.
9. The method for preparing boron-based composite particles containing high-energy compounds according to claim 1, characterized in that: The mixed solution was added into the surfactant solution at 60-65°C by dropwise addition.
10. Boron-based composite microparticles containing high-energy compounds prepared according to the method according to any one of claims 1 to 9.